Mechanical and Microstructural Evaluation of Fly Ash–GGBFS Alkali Activators Reinforced with Steel and Polypropylene Fibers - Amit Kumar (International Journal of Intelligent Systems and Applications in Engineering, 2025)
The experimental investigation was carried out to examine how polypropylene (PP) and steel Fibers (SF) influence the microstructural characteristics and mechanical response of fly ash (FA) and ground granulated blast furnace slag (GGBFS)–based alkali-activated mortars. In this study, FA and GGBFS, both obtained as industrial by-products, served as the main aluminosilicate precursors for synthesizing the binder matrix. Various Fiber volume fractions of PP and SF were incorporated to evaluate their effects on compressive strength, splitting tensile strength, and flexural performance. The compressive elastic modulus was estimated using an empirical model derived from the experimentally determined compressive strength (CS) values of the Fiber-reinforced mixtures. Results revealed that adding PP Fibers up to approximately 2.35% by volume led to a notable enhancement in flexural strength and deformation resistance. On the other hand, incorporating 2.25% SF resulted in the highest compressive strength, showing an improvement of 14.15% compared with the control mix. Both PP- and SF-reinforced mortars displayed a progressive rise in flexural toughness index with increasing Fiber dosage, although the enhancement was more pronounced in the SF composites, highlighting their superior crack-bridging efficiency and energy absorption capacity.